Hubungan Pengetahuan dengan Motivasi Ibu Hamil Melaksanakan Triple Eliminasi untuk Menurunkan Penularan Penyakit Dari Ibu Ke Anak - Dewa Ayu Sutarini; Ni Wayan Manik Parwati; Putu Ayu Ratna Darmayanti (Universitas Malahayati Lampung, 2025)
ABSTRACT The prevalence of HIV cases among pregnant women in Indonesia in 2021 showed 0.18% of pregnant women had HIV positive, the percentage of pregnant women being tested for HIV was 82.0%, and the results of the Hepatitis B surface Antigen (HBsAg) examination in 2021 was 1.6% of pregnant women are reactive with the percentage of Hepatitis B tests in pregnant women being 60.3% (Ministry of Health of the Republic of Indonesia, 2022). Bali Province places the seventh position with the highest number of HIV cases in pregnant women at 0.31% with a screening percentage of 82.0%, and reactive Hepatitis B cases at 1.2% (Ministry of Health of the Republic of Indonesia, 2022). So, it is necessary to stop the transmission of infectious diseases HIV, Syphilis and Hepatitis B from mother to child through Triple Elimination examination. To determine the correlation between knowledge and pregnant mother’s motivation to do triple elimination to decrease infectious disease from mother to child in public Health Center Mengwi II. This study employed quantitative research. It was analytical correlational design with cross sectional study. The population was 313 pregnant women who checked up her pregnancy. There were 76 respondents recruited as the samples which were chosen by using non-probability sampling such as purposive sampling. The data were collected by using questionnaire. The validity test used was face validity. The data were analyzed by using bivariate and Rank Spearman test. The result showed that 58 respondents had good knowledge, 11 respondents had sufficient knowledge, and 7 respondents had poor knowledge. There were 56 respondents had good motivation, 19 respondents had moderate motivation, and 1 respondent had less motivation. The result of p-value was 0,078 0,05 and coefficient correlation (r = 0,204). There was not correlation between motivation of pregnant women doing triple elimination to decrease infectious disease from mother to child in Public Health Center Mengwi II. It is expected the health workers to inform pregnant women related to triple elimination. Keywords: Triple Elimination, Pregnancy, Syphilis, HIV ABSTRAK Prevalensi kasus HIV pada ibu hamil di Indonesia pada tahun 2021, terdapat 0,18% ibu hamil yang positif HIV, dengan persentase ibu hamil yang diperiksa HIV sebesar 82,0%, dan hasil pemeriksaan Hepatitis B surface Antigen (HBsAg) tahun 2021 sebanyak 1,6% ibu hamil reaktif dengan persentaase pemeriksaan Hepatitis B pada ibu hamil sebesar 60,3% (Kemenkes RI, 2022). Provinsi Bali menduduki posisi ke tujuh kasus HIV terbanyak pada ibu hamil dengan jumlah 0,31 % dengan persentase pemeriksan 82,0%, dan kasus Hepatitis B reaktif sebanyak 1,2 % (Kemenkes RI, 2022) sehingga perlu untuk memutus rantai penularan penyakit infeksi HIV, Sifilis dan Hepatitis B dari ibu ke anak melalui pemeriksaan Triple Eliminasi. Mengetahui hubungan pengetahuan dengan motivasi ibu hamil melaksanakan triple eliminasi untuk menurunkan kejadian penularan penyakit dari ibu ke anak di UPTD Puskesmas Mengwi II. Penelitian adalah penelitian kuantitatif dengan menggunakan analitik korelatif. Rancangan penelitian yaitu potong lintang, Populasi penelitian keseluruhan ibu hamil yang memeriksakan kehamilan sejumlah 313 orang. Sampel sebanyak 76 responden. Metode sampling yang digunakan yakni non-probability sampling yaitu purposive sampling. Alat pengumpulan data dengan kuesioner. Uji validitas dengan menggunakan face validity. Analisis bivariat dengan uji Rank Spearman sebab data tidak berdistribusi normal. Pengetahuan terbanyak adalah kategori baik yaitu 58 orang (76,3%), kategori cukup 11 orang (14,5%), kategori kurang 7 orang (9,2%). Motivasi terbanyak yaitu motivasi baik sebanyak 56 orang (73,7%), motivasi cukup 19 orang (25%) motivasi kurang 1 orang (1,3%). Hasil p-value = 0,078 0,05 dan nilai koefisien korelasi (r = 0,204). Tidak ada hubungan antara pengetahuan dengan motivasi ibu hamil melaksanakan triple eliminasi untuk menurunkan kejadian penularan penyakit dari ibu ke anak di UPTD Puskesmas Mengwi II. Diharapkan tenaga kesehatan selalu menginformasikan kepada ibu hamil terkait pemeriksaan triple eliminasi. Kata Kunci: Triple Eliminasi, Kehamilan, Sifilis, HIV